EXPERIMENTAL JUSTIFICATION OF THE METHODOLOGICAL SYSTEM OF PREPARING FUTURE COMPUTER SCIENCE TEACHERS FOR TEACHING ROBOTICS - Bidaibekov, Е.Ы.; Pak, Н.И.; Salgozha, И.Т.; Kozhagul, А.Т. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2025)
The article presents the results of a pedagogical experiment aimed at evaluating the effectiveness of an original methodological system for preparing future computer science teachers to teach educational robotics. The developed system combines a project-based learning approach, the use of an online course, and practical training through the completion of educational projects and the creation of a methodological portfolio. The experiment involved students from a pedagogical university, divided into control and experimental groups. Both groups completed the training course and undertook teaching practice, during which they taught schoolchildren the basics of robotics. Post-experiment diagnostics assessed the students’ methodological readiness and the level of robotics proficiency achieved by the schoolchildren. The analysis employed level-based indicators, average scores, and the Pearson χ² criterion. The results demonstrated that the experimental group of students achieved a higher level of methodological preparedness, and their pupils showed better outcomes in final project tasks. These findings confirm the effectiveness of the proposed system and support its integration into teacher training programs in digital and engineering disciplines.